Religion and LGBTQ sexualities: critical essays - Hunt, Stephen (Routledge, 2024)
This compiled and edited collection engages with a theme which is increasingly attracting scholarly attention, namely, religion and LGBTQ sexuality. Each section of the volume provides perspectives to understanding academic discourse and wide-ranging debates around LGBTQ sexualities and religion and spirituality. The collection also draws attention to aspects of religiosity that shape the lived experiences of LGBTQ people and shows how sexual orientation forges dimensions of faith and spirituality. Taken together the essays represent an exploration of contestations around sexual diversity in the major religions; the search of sexual minorities for spiritual 'safe spaces' in both established and new forms of religiosity; and spiritual paths formed in reconciling and expressing faith and sexual orientation. This collection, which features contributions from a number of disciplines including sociology, anthropology, psychology, history, religious studies and theology, provides an indispensable teaching resource for educators and students in an era when LGBTQ topics are increasingly finding their way onto numerous undergraduate, post-graduate and profession orientated programmes.